2017
DOI: 10.1097/mnm.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

Common malignant brain tumors

Abstract: Central nervous system lymphomas can be differentiated from GBM and metastases by their higher metabolic activity. In addition, F-FDG PET/CT can potentially impact therapeutic decisions by detecting primary malignancy in patients with metastatic brain lesions and extracranial disease sites in patients with brain lymphoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…18 F-FDG-PET has proven to be a reliable clinical diagnostic tool for CNS lymphoma and GBM. Previous studies on the differentiation of CNS lymphoma from GBM mainly utilized quantitative parameters such as SUVmax or the T/N ratio and reached an AUC of approximately 0.90(Yamaguchi et al, 2014; Purandare et al, 2017; Zhou et al, 2018). Our study demonstrated a similar result, with AUC of SUVmax reached 0.943 and AUC of the T/N ratio reached 0.870 using a single feature threshold-based simple classifier (consistent with previous studies).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-FDG-PET has proven to be a reliable clinical diagnostic tool for CNS lymphoma and GBM. Previous studies on the differentiation of CNS lymphoma from GBM mainly utilized quantitative parameters such as SUVmax or the T/N ratio and reached an AUC of approximately 0.90(Yamaguchi et al, 2014; Purandare et al, 2017; Zhou et al, 2018). Our study demonstrated a similar result, with AUC of SUVmax reached 0.943 and AUC of the T/N ratio reached 0.870 using a single feature threshold-based simple classifier (consistent with previous studies).…”
Section: Discussionmentioning
confidence: 99%
“…CNS lymphomas usually have a relatively high tumor cell density and increased glucose metabolism, resulting in an increased standardized uptake value (SUV)(Kawai et al, 2005; Kasenda et al, 2013; El-Galaly et al, 2018). Although few studies have investigated the role of 18 F-FDG-PET for distinguishing CNS lymphoma from GBM(Yamaguchi et al, 2014; Purandare et al, 2017; Zhou et al, 2018), the parameters involved in these studies have been mostly restricted to specific features, such as the maximum SUV (SUVmax) and tumor-to-normal contralateral cortex activity (T/N) ratio, which can hardly display the characteristics of the whole tumor.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological SUVs of lung tissue were 0.37–1.29, similar to those previously reported ( 33 – 35 ). The numerical value is associated with the differentiation of tumor cells, in addition to the activity and the degree of malignancy ( 36 38 ). In order to minimize variation and ensure reproducibility, sites where increased SUV value was considered as physiological uptake were excluded and the maximal pixel activity in the ROI was the SUV max ( 34 , 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…showed no difference in SUV max values for HGG and BM whereas SUV max of 15.5 showed sensitivity and specificity of 84% and 80% for diagnosing PCNSL. [18] Two similar studies have shown the similar cutoff for detecting PCNSL, but false positives have been reported, owing to lack of specificity. [1920] The need of specific tracer is important since not all lesions are amenable to biopsy, and treatment plans are based on imaging diagnosis.…”
Section: Discussionmentioning
confidence: 99%